The Case Against JIVE - Russell Davidson; James G. MacKinnon (Queen's University, Department of Economics, 2004)
We perform an extensive series of Monte Carlo experiments to compare the performance of two variants of the "Jackknife Instrumental Variables Estimator," or JIVE, with that of the more familiar 2SLS and LIML estimators. We find no evidence to suggest that JIVE should ever be used. It is always more dispersed than 2SLS, often very much so, and it is almost always inferior to LIML in all respects. Interestingly, JIVE seems to perform particularly badly when the instruments are weak.
Keywords: C12; C15; C30; 330; two-stage least squares; LIML; JIVE; instrumental variables; weak instruments; IV-Schätzung; Monte-Carlo-Simulation; Theorie